Experimental Optimization of Annular Polishing Parameters for Silicon Carbide - Yuan Liu; La Han; Haiying Liu; Yikai Shi; Junjie Zhang (Advances in Materials Science and Engineering)
Machined surface quality has a strong impact on the functionality of silicon carbide-based components and devices. In the present work, we first analytically investigate the complex coupling of motions in annular polishing based on the Preston equation, which derives the influential parameters for material removal. Subsequently, we conduct systematic annular polishing experiments of reaction-bonded silicon carbide to investigate the influence of derived parameters on polished surface quality, which yield optimized polishing parameters for achieving ultralow surface roughness of reaction-bonded silicon carbide.